Comparison of Non‐Coding RNAs in Exosomes and Functional Efficacy of Human Embryonic Stem Cell‐ versus Induced Pluripotent Stem Cell‐Derived Cardiomyocytes. (31st July 2017) - Lee, Won Hee; Chen, Wen‐Yi; Shao, Ning‐Yi; Xiao, Dan; Qin, Xulei; Baker, Natalie; Bae, Hye Ryeong; Wei, Tzu‐Tang; Wang, Yongjun; Shukla, Praveen; Wu, Haodi; Kodo, Kazuki; et al.
Abstract: Both human embryonic stem cell‐derived cardiomyocytes (ESC‐CMs) and human induced pluripotent stem cell‐derived CMs (iPSC‐CMs) can serve as unlimited cell sources for cardiac regenerative therapy. However, the functional equivalency between human ESC‐CMs and iPSC‐CMs for cardiac regenerative therapy has not been demonstrated. Here, we performed a head‐to‐head comparison of ESC‐CMs and iPSC‐CMs in their ability to restore cardiac function in a rat myocardial infarction (MI) model as well as their exosomal secretome. Human ESCs and iPSCs were differentiated into CMs using small molecule inhibitors. Fluorescence‐activated cell sorting analysis confirmed ∼85% and ∼83% of CMs differentiated from ESCs and iPSCs, respectively, were positive for cardiac troponin T. At a single‐cell level, both cell types displayed similar calcium handling and electrophysiological properties, with gene expression comparable with the human fetal heart marked by striated sarcomeres. Sub‐acute transplantation of ESC‐CMs and iPSC‐CMs into nude rats post‐MI improved cardiac function, which was associated with increased expression of angiogenic genes in vitro following hypoxia. Profiling of exosomal microRNAs (miRs) and long non‐coding RNAs (lncRNAs) revealed that both groups contain an identical repertoire of miRs and lncRNAs, including some that are known to be cardioprotective. We demonstrate that both ESC‐CMs and iPSC‐CMs can facilitate comparable cardiac repair. This is advantageous because, unlike allogeneic ESC‐CMs used in therapy, autologous iPSC‐CMs could potentially avoid immune rejection when used for cardiac cell transplantation in the future. Stem Cells 2017;35:2138–2149 Abstract : Both human embryonic stem cell‐derived cardiomyocytes (ESC‐CMs) and human induced pluripotent stem cell‐derived cardiomyocytes (iPSC‐CMs) facilitate comparable functional recovery following transplantation into infarcted hearts. Exosomal profiling revealed highly similar microRNA and long non‐coding RNA contents between exosomes from ESC‐CMs and iPSC‐CMs and may represent an alternative to direct cell therapy in the future.